Analisis Implementasi Gaya Komunikasi Pemimpin Laki-Laki di Era Virtual: Studi Kasus pada Rudi Kowek Casting Space - Dlia Luzain Deani; Mega Rahmat Katulistiwa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the implementation of male leaders' communication styles in virtual environments in organizational activities, using a case study at Rudi Kowek Casting Space. The focus of the study includes identifying the specifics of gender-based communication styles, decision-making strategies, and subordinates' perceptions of the effectiveness of virtual leadership. The theories used include Organizational Communication Theory, Gender Communication Theory, Transformational and Transactional Leadership Theory, and Feminism and Masculinity in Leadership Theory. The research method is qualitative, with data collection techniques using in-depth interviews with one core informant (Casting Director) and one supporting informant (staff). Data were analyzed thematically based on a conceptual framework that encompasses dimensions of leadership communication (verbal, non-verbal, written, directive, participatory), socio-cultural factors, and indicators of communication effectiveness. The results show that male leaders tend to combine masculine (assertive, directive) and feminine (empathic, participatory) styles to adapt to virtual challenges, such as maintaining a human touch in digital communication. However, gender stereotypes continue to influence perceptions of effectiveness, with men's assertiveness often perceived as more competent, while women's empathy is perceived as less strategic. These findings reinforce the importance of adaptive androgynous leadership in the virtual era.